Adsorpsi Logam Cd, Cu Dan Pb Dengan Menggunakan Hidroksiapatit (HA) Sebagai Adsorben - Kendro Prasetyo; Yelmida Azis; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study investigated the ability of hydroxyapatite (HA) to adsorb aqueous Cd2+, Pb2+ and Cu2+ metal ions from single-metal and multi-metal ions reaction systems. Hydroxyapatite as adsorbent made from wasted-eggshell through precipitate calcium carbonate (PCC) processes. Based on AAS as intrumentation, show that in single metal ions adsorption, the sorption affinity of HA for Pb(II) is always higher than that for Cu(II) and for Cd(II); the sorption maxima for the Cd2+, Pb2+ and Cu2+ metal ions follow the order Pb2+ > Cu2+ > Cd2+. The greatest sorption percentage of Pb(II) is 99,338% ; Cu(II) is 95,403% and Cd(II) is 86,343%. The sorption affinity of HA for metal ions follow the order Pb2+ > Cu2+ > Cd2+ , this could be inversely proportional to the hydrated ionic radii as Pb2+ (4.01 Å) < Cu2+ (4.19 Å) < Cd2+ (4.26 Å).Keywords: hydroxyapatite (HA), Cd, Pb, Cu, competitive adsorption, adsorption selectivity, hydrated ionic radii